Utilization of Digital E-Commerce Businesses for Micro, Small and Medium Enterprises (Umkm) in Sinjai Regency - Makmur Makmur; Sulina Sulina (Jurnal Ilmu Manajemen Profitability, 2023)
This study aims to find out how the untilization of digital E-commerce Business for mircro, small and Medium Enterprises in Sinjai Regency. The type of research used is a qualitative method with a descriptive format, the data collection techniques used in this study include: observation, interviews, documemntation, data analysis techniques used are data collection, data reduction and concusion drawing. In the Utilization of Digital E-commerce Business For mircro, small and Medium Enterprises in Sinjai Regency by the office of Cooperatives for small micro Business and Manpower JL. Jendral Sudirman, Blangnipa, North Sinjai, Sinjai Regency. The author has studied the indicators that support the achievement of Digital E-commerce Business Utilization for micro, small and medium Enterprises among, others, namely the use of MSME product  E- commerce, the first of which will be wider (global) sales, reduce the use of infrastructure and reduce costs. From the result of research on the Utilization of Digital E-commerce Business for micro, small and medium Enterprises in Sinjai Regency, in terms of the use of E-commerce such as online marketing their products/sales. And provide a very significant effect in the sense that it generates a lot of profits for business owners so that the perpetrators of micro, small and medium Enterprises in Sinjai Regency will be more advanced and develop rapidly.